Pressure vessel and stacks field repair manual : - Escoe, A. Keith (Elsevier/Butterworth-Heinemann, 2008)
Written from the practitioner's perspective, this book is designed as a companion for engineers who are working in the field and faced with various problems related to pressure vessels and stacks, such as: modification, retrofitting existing pressure vessels or stacks to either enhance process capability, lift, move or replace damaged equipment. This makes the book a valuable guide for new engineers who need to develop a feel for these types of operations or more experienced engineers who wish to acquire more useful tips, this handy manual provides the readers with rules of thumbs and tips to mitigate or remediate problems which can occur on a daily bases.